(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In a population of Aiolopus thalassinus (Fabricius, 1781), originated from East Africa, (Kenya), and reared successfully under controlled laboratory conditions at Hannover, the effects of factors controlling reproduction were investigated. The reproductive parameters, like the number of ovariols, period of preoviposition, number of egg pods per female, as well as the changes in the volume of corpora allata (CA), the juvenile hormone (JH) titre of the haemolymph, and the growth of the terminal (t) and subterminal oocytes were studied throughout the egg-laying period. For the data of each reproductive parameter, 58-103 females were used. Up to 22 consecutive gonadotropic cycles per female were evaluated. Neither a correlation was found between the volume of CA and the age of the adult females, nor between these parameters and the size of the t-oocytes. The JH-III titre of the haemolymph was low (< 0.2 pmol/10 μl) during previtellogenesis, increasing after that to a maximum of 2.5 pmol/10 μland declining drastically with the maturation of the oocytes and the onset of oviposition. After the first egg deposition, the JH-III titre of the haemolymph increased again with the growth of the oocytes in the gonadotropic cycles, but did not start from that low level found during previtellogenesis, and did not show the high values recorded before the first oviposition, when the volume of t-oocytes increased. The growth of the subterminated oocytes often started before deposition of the t-oocytes. The JH-III titre of these individuals did not drastically decline. The simultaneous ripening of two generations of oocytes might account for the short interval of only one or two days passing between two ovipositions. Before the termination of the 2nd gonadotropic cycle, the JH-III titre declined again, but no clear cyclisation of the JH-III titre was found in the haemolyph. Under laboratory conditions, the East African A. thalassinus showed a high fecundity with an average of 36 ovarioles and the possibility to deposite more than 20 egg pods per female. The CA volume varied independently of the JH-III titre of the haemolymph and cannot be considered as a reliable indicator for the latter. The increase of the CA volume, accompanied by a simultaneous rise of the JH titre of the haemolyph, could only be observed during the first 15 days after emergence. In some females, a growth of oocytes was found neither before nor after the first oviposition, even though some of them had a very high JH-III titre in the haemolymph.